Interference of simultaneous vaccination against avian metapneumovirus, infectious bronchitis, and Newcastle disease in broilers - Palomino T., Víctor (2011)
The study evaluated the interference in the immune protection system against Newcastle disease (ENC) caused by the vaccination against Avian Metapneumovirus (aMPV) in a simultaneous vaccination against ENC and Infectious Bronchitis (BI) in oneday- old broilers. Four hundred Cobb-Vantress 500 broilers were distributed into four groups. Group I vaccinated at 1-day-old against BI (H120), ENC (VG/GA) and aMPV (11/ 94) with revaccination at day 9 against ENC (VG/GA). Group II vaccinated at 1-day-old against BI (Ma5), ENC (C2) and aMPV (11/94) and revaccinated at day 9 against ENC (Clone 30). Group III vaccinated at 1-day-old against BI and ENC (VG/GA) and revaccinated at day 9 against ENC (VG/GA). Group IV received no vaccine. All groups were challenged at day 30 with a velogenic viscerotropic strain of ENC virus. Mortality, clinical signs, serologic response, post-vaccination reaction, and productive performance were evaluated. Mortality was 12 and 16% for groups vaccinated against aMPV versus 23% for the non-vaccinated group against aMPV, and 88% for the control group; however, no significant difference was found between the three vaccinated groups. Findings indicate that vaccination against aMPV in broilers did not cause interference in the protection against ENC in any of the vaccinated groups; besides, there was less post-vaccination reaction with the enteric strain vaccine instead of a respiratory strain of ENC.